2021
DOI: 10.3390/ijerph18179402
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Culturally Anchored Qualitative Approach to Conduct and Analyze Focus Group Narratives Collected in Diné (Navajo) Communities to Understand the Impacts of the Gold King Mine Spill of 2015

Abstract: The Gold King Mine Spill (Spill) occurred in August 2015 upstream from Silverton, Colorado and released three million gallons of contaminated water into the Animas River, a tributary to the San Juan River that flows across the Navajo Nation. Using principles of community-engaged research, the Gold King Mine Spill Diné Exposure Project co-developed a culturally anchored approach to conduct focus groups and analyze narratives collected in three Diné (Navajo) communities along the San Juan River within 9 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Four of these articles were focused on the Mohawk community of Akwesasne (Table S6), and they documented a range of chronic and developmental outcomes associated with exposure to chemical stressors (primarily lead and PCBs), including early menarche, heart disease, kidney disease, diabetes, and hypertension. In four qualitative peer-reviewed studies, culture, spirituality, language, and community were found to be adversely influenced by contaminated site exposure (Cassady, 2007;Hoover, 2013;Smith et al, 2010;Teufel-Shone et al, 2021), and these are social and environmental determinants of Indigenous Peoples' health (Reading & Wien, 2009). There was evidence that many Indigenous communities face long-term site-related challenges including a changing relationship to the earth, fear related to contamination, and cultural loss (Moore-Nall, 2015; John Sandlos & Arn Keeling, 2016;Smith et al, 2010;Teufel-Shone et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of these articles were focused on the Mohawk community of Akwesasne (Table S6), and they documented a range of chronic and developmental outcomes associated with exposure to chemical stressors (primarily lead and PCBs), including early menarche, heart disease, kidney disease, diabetes, and hypertension. In four qualitative peer-reviewed studies, culture, spirituality, language, and community were found to be adversely influenced by contaminated site exposure (Cassady, 2007;Hoover, 2013;Smith et al, 2010;Teufel-Shone et al, 2021), and these are social and environmental determinants of Indigenous Peoples' health (Reading & Wien, 2009). There was evidence that many Indigenous communities face long-term site-related challenges including a changing relationship to the earth, fear related to contamination, and cultural loss (Moore-Nall, 2015; John Sandlos & Arn Keeling, 2016;Smith et al, 2010;Teufel-Shone et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four peer-reviewed articles explored the impacts of contaminated sites on Indigenous peoples using qualitative interviews (Table S7) (Cassady, 2007;Hoover, 2013;Smith et al, 2010;Teufel-Shone et al, 2021). In the case of the Aamjiwnaang First Nation (Ontario), semi-structured interviews of 18 community members were conducted, with interviewees reporting fear related to contamination, unknown long-term health effects, and a changing relationship to the earth resulting from a large contaminated site nearby ("Chemical Valley") (Smith et al, 2010).…”
Section: Contaminated Sites and The Health Of Indigenous Peoplesmentioning
confidence: 99%
See 3 more Smart Citations